2003
DOI: 10.1053/jlts.2003.50149
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged survival of rat liver allograft with adenoviral gene transfection of human immunodeficiency virus type 1 nef

Abstract: HIV-1 nef is believed to allow immune evasion by modifying cell surface molecules because of certain mechanisms such as downregulation of the major histocompatibility complex (MHC) class I molecule complex as well as upregulation of FasL. In the present study, we successfully generated a recombinant adenovirus vector containing HIV-1 nef. We detected the expression of nef in liver infected with AxCANef by immune staining and Western blotting, and confirmed its expression as persistent for more than 4 weeks. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
0
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
4
0
0
Order By: Relevance
“…1). In agreement with the control group, historical data from our group 16 and others 17,18 indicate that liver allograft rejection in Lewis recipients of DA livers occurs 10 to 14 days post-transplant. The livers of 2 TLI-treated allograft recipients were rejected within the first 30 days post-transplant, with no other livers rejected thereafter.…”
Section: Posttransplant Tli Alone Can Prolong the Survival Of Rat LIVsupporting
confidence: 89%
“…1). In agreement with the control group, historical data from our group 16 and others 17,18 indicate that liver allograft rejection in Lewis recipients of DA livers occurs 10 to 14 days post-transplant. The livers of 2 TLI-treated allograft recipients were rejected within the first 30 days post-transplant, with no other livers rejected thereafter.…”
Section: Posttransplant Tli Alone Can Prolong the Survival Of Rat LIVsupporting
confidence: 89%
“…It has been reported that DA-LEW is a rat liver transplant model with a high rejection rate, 12,13 and a mean survival time (without drugs) of approximately 11 days has been reported. 14 The control results of the present study are in accordance with this. The hCTLA4Ig gene transfer group, however, had a significantly longer survival period, and only mild to moderate rejection reactions were observed in the allograft, which confirms that hCTLA4Ig gene transferred by intramuscular injection was valid for blocking the co-stimulatory signals of the immune response to allografts.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with the report from both our group and others [19], the liver allograft rejection in LEW recipients of DA livers occurs within 14 days post-transplant in control groups, as shown in the historical data.…”
Section: Survival Rate For Transplant Recipientssupporting
confidence: 93%
“…To evaluate the effect of a combination of MSCs and IL-10 on recipient survival, we injected the IL-10-engineered MSCs into the liver allograft through the jugular vein. In agreement with the report from both our group and others [19], the liver allograft rejection in LEW recipients of DA livers occurs within 14 days post-transplant in control groups, as shown in the historical data.…”
Section: Survival Rate For Transplant Recipientssupporting
confidence: 93%